Composite negative electrode material, preparation method thereof and battery

By filling silicon-based materials in the pores of carbon materials and controlling the porosity, the problems of low specific capacity and volume expansion of the negative electrode material of lithium-ion batteries are solved, and the circulation performance and structural stability of the battery are improved.

CN119230767APending Publication Date: 2024-12-31BTR NEW MATERIAL GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310784881.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The theoretical specific capacity of the negative electrode material of traditional lithium-ion batteries is lower, and the volume expansion is severe during lithium alloying, resulting in structural collapse and increased side reactions, affecting electrochemical performance.

Method used

Using composite negative electrode material, by filling silicon-based materials in the pores of carbon materials, the silicon-based materials are evenly filled with the structure of gradually shrinking the pore size of the carbon materials, and the opening pores of the holes are controlled to be between 2% and 20%, so as to improve the structure of the material. Stability and cycling performance.

Benefits of technology

The specific capacity and density of composite negative electrode materials are improved, structural collapse and side reactions caused by volume expansion are reduced, and cycling and electrochemical properties are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230767A_ABST
    Figure CN119230767A_ABST
Patent Text Reader

Abstract

The invention relates to a composite negative electrode material and a preparation method thereof and a battery, the composite negative electrode material comprises a carbon material and a silicon-based material, the carbon material is provided with holes, the aperture of at least part of the holes is gradually reduced from the surface of the carbon material to the inside, and at least part of the silicon-based material is filled in the holes. And the opening porosity of holes in the composite negative electrode material is 2-20%. According to the composite negative electrode material disclosed by the invention, the silicon-based material is filled in the holes of the carbon material, so that the structural stability of the material can be improved, the collapse of the material structure caused by volume expansion in the lithium intercalation and deintercalation process is reduced, and the occurrence of side reactions is effectively reduced, thereby improving the cycle performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of negative electrode materials technology, and in particular to composite negative electrode materials, their preparation methods, and batteries. Background Technology

[0002] Lithium-ion batteries possess advantages such as high energy density, long cycle life, low environmental pollution, and no memory effect, making them widely used in electric vehicles and consumer electronics. Traditional carbon anode materials have limited their widespread application due to their relatively low theoretical specific capacity (372 mAh / g). To improve the energy density of lithium-ion batteries, researchers have begun searching for high-capacity anode materials, with silicon-based anode materials gradually becoming a research hotspot due to their theoretical specific capacity reaching 4200 mAh / g.

[0003] However, silicon-based anode materials undergo significant volume expansion during the alloying process with lithium. Furthermore, as cycling progresses, silicon-based anode materials experience degradation mechanisms such as pulverization, contact loss with conductive agents and current collectors, and the formation of an unstable solid electrolyte interface (SEI), leading to a deterioration in the electrochemical performance of the anode materials. Summary of the Invention

[0004] Therefore, the purpose of this application is to provide a composite anode material and its preparation method, as well as a battery. In the composite anode material of this application, silicon-based material is filled in the pores of carbon material, which can improve the structural stability of the material, reduce the collapse of the material structure caused by volume expansion during lithium insertion and extraction, effectively reduce the occurrence of side reactions, and thus improve the cycle performance of the material.

[0005] In a first aspect, this application provides a composite anode material comprising a carbon material and a silicon-based material, wherein the carbon material has pores, at least a portion of which have a gradually decreasing pore size from the surface to the interior of the carbon material, and at least a portion of which is filled with the silicon-based material, and the open porosity of the pores in the composite anode material is 2% to 20%.

[0006] In some embodiments, the specific surface area of ​​the carbon material is 300 m². 2 / g~2500m 2 / g.

[0007] In some embodiments, the pore volume of all pores in the carbon material is 0.4 cm³. 3 / g~1.8cm 3 / g.

[0008] In some embodiments, the density of the carbon material is ≤1.50 g / cm³. 3 .

[0009] In some embodiments, the pore density in the carbon material is 1 pore / μm.2 ~1000 / μm 2 .

[0010] In some embodiments, the average pore size of the carbon material is 0.1 nm to 50 nm.

[0011] In some embodiments, the porosity of the carbon material is 45% to 75%.

[0012] In some embodiments, the pore fill rate is ≥70%.

[0013] In some embodiments, in a carbon material, for three holes that are not on the same straight line, the diameters of the three holes are d1, d2, and d3, and the hole spacings are l1, l2, and l3, respectively, and A1 is defined as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in the range is given by B1 as d1 + d2 + d3 and C1 as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The maximum value in the range is B1 / C1 > 1, and B1 / A1 ≤ 4.

[0014] In some embodiments, the pores in the carbon material include micropores, mesopores, and macropores, wherein the micropores account for 5% to 70% of the total volume of all pores, the mesopores account for 30% to 90% of the total volume of all pores, and the macropores account for 0% to 5% of the total volume of all pores.

[0015] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 2 nm to 20 nm in all mesopores is >90%.

[0016] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 5 nm to 20 nm in all mesopores is 10% to 50%.

[0017] In some embodiments, the cross-section of the hole is funnel-shaped or inverted conical.

[0018] In some embodiments, the silicon-based material accounts for 15%-60% of the mass of the composite anode material.

[0019] In some embodiments, the particle size of the silicon-based material is <50 nm.

[0020] In some embodiments, the silicon-based material includes at least one of crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline and amorphous silicon.

[0021] In some embodiments, the silicon-based material includes amorphous silicon.

[0022] In some embodiments, the specific surface area of ​​the composite negative electrode material is 2m². 2 / g~500m 2 / g.

[0023] In some embodiments, the pore volume of the composite negative electrode material is 0.001 cm³. 3 / g~0.6cm 3 / g.

[0024] In some embodiments, the volume percentage of pores in the composite negative electrode material is ≤20%.

[0025] In some embodiments, the density of the composite negative electrode material is 1.9 g / cm³. 3 ~2.3g / cm 3 .

[0026] In some embodiments, the porosity of the composite negative electrode material is 5% to 20%.

[0027] In some embodiments, the pore size of the composite negative electrode material is D nm, where D ranges from 0.5 to 100.

[0028] In some embodiments, in the composite negative electrode material, the pore spacing between any two adjacent pores is L nm, where L ranges from 1 to 300.

[0029] In some embodiments, the pore diameter of the composite negative electrode material is D nm, the pore spacing between any two adjacent pores is L nm, and L≥4×D.

[0030] In some embodiments, in the composite negative electrode material, for three holes that are not on the same straight line, the diameters of the three holes are D1, D2, and D3, and the hole spacings are L1, L2, and L3, respectively. A2 is defined as L1. 2 -(L2 / 2) 2 L1 2 -(L3 / 2) 2 L2 2 -(L1 / 2) 2 L2 2 -(L3 / 2) 2 L3 2 -(L1 / 2) 2 or L3 2 -(L2 / 2) 2 The minimum value in the equation is B2, which is D1+D2+D3, and 3<A2 / B2<50.

[0031] In some embodiments, the carbon material is tested using an N2 adsorption-desorption method, and it exhibits a peak value Q1 in the range of 2 nm to 50 nm. The composite anode material is also tested using the same N2 adsorption-desorption method, and it exhibits a peak value Q2 in the range of 2 nm to 50 nm, satisfying the relationship Q2 / Q1 ≤ 0.6. In some embodiments, the mass percentage of oxygen in the composite anode material is ≤ 10 wt%.

[0032] Secondly, this application provides a method for preparing a composite negative electrode material, comprising the following steps:

[0033] A porous carbon material is provided, and a reaction gas containing silicon source gas and hydrogen is introduced under negative pressure. Vapor phase deposition is then performed on the carbon material to obtain a composite anode material. The composite anode material comprises a carbon material and a silicon-based material. At least a portion of the pores in the carbon material have a gradually decreasing pore size from the surface to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 2% to 20%.

[0034] In some embodiments, the specific surface area of ​​the carbon material is 300 m². 2 / g~2500m 2 / g.

[0035] In some embodiments, the pore volume of all pores in the carbon material is 0.4 cm³. 3 / g~1.8cm 3 / g.

[0036] In some embodiments, the density of the carbon material is ≤1.50 g / cm³. 3 .

[0037] In some embodiments, the pore density in the carbon material is 1 pore / μm. 2 ~1000 / μm 2 .

[0038] In some embodiments, the average pore size of the carbon material is 0.1 nm to 50 nm.

[0039] In some embodiments, the porosity of the carbon material is 45% to 75%.

[0040] In some embodiments, the pore fill rate is ≥70%.

[0041] In some embodiments, in a carbon material, for three holes that are not on the same straight line, the diameters of the three holes are d1, d2, and d3, and the hole spacings are l1, l2, and l3, respectively, and A1 is defined as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in the range is given by B1 as d1 + d2 + d3 and C1 as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The maximum value in the range, and B1 / C1>1, and B1 / A1≤4.

[0042] In some embodiments, the pores in the carbon material include micropores, mesopores, and macropores, wherein the micropores account for 5% to 70% of the total volume of all pores, the mesopores account for 30% to 90% of the total volume of all pores, and the macropores account for 0% to 5% of the total volume of all pores.

[0043] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 2 nm to 20 nm in all mesopores is >90%.

[0044] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 5 nm to 20 nm in all mesopores is 10% to 50%.

[0045] In some embodiments, the cross-section of the hole is funnel-shaped or conical.

[0046] In some embodiments, the deposition temperature of the vapor deposition is 400°C to 650°C.

[0047] In some embodiments, the heating rate of the vapor deposition is 2°C / min to 20°C / min.

[0048] In some embodiments, the deposition pressure of the vapor deposition is 0.1 kPa to 50 kPa.

[0049] In some embodiments, the deposition time of the vapor phase deposition is 2h to 1000h.

[0050] In some embodiments, the vapor deposition is performed under a protective atmosphere.

[0051] In some embodiments, the protective atmosphere includes at least one of nitrogen, argon, helium, neon, krypton, and xenon.

[0052] In some embodiments, the raw materials for the silicon source gas include at least one of silane, silane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.

[0053] In some embodiments, the volume percentage of hydrogen in the reaction gas containing silicon source gas and hydrogen is 50% to 98%.

[0054] In some embodiments, the vapor deposition is performed under a protective atmosphere, wherein the volume ratio of the protective atmosphere to the reactant gas is 1:10 to 10:1.

[0055] In some embodiments, before introducing the reaction gas containing silicon source gas under negative pressure, the method further includes the following steps: evacuating a vacuum, stopping the vacuuming when the deposition pressure of the vapor deposition reaches 0.1 kPa to 50 kPa; and then introducing a protective atmosphere to control the oxygen content in the vapor deposition reaction chamber to be <5%.

[0056] In some embodiments, the method further includes the following steps: cooling, washing and drying the reaction products of vapor deposition to obtain a composite anode material.

[0057] In some embodiments, the washing method includes ultrasonic cleaning.

[0058] In some embodiments, the solvent used for washing includes anhydrous ethanol.

[0059] In some embodiments, the washing time is 30 min to 60 min.

[0060] In some embodiments, the drying process takes 20 to 100 minutes.

[0061] In some embodiments, the drying process is carried out at a temperature of 70°C to 90°C.

[0062] Thirdly, this application provides a battery comprising the composite negative electrode material described in the first aspect or the composite negative electrode material prepared by the preparation method described in the second aspect.

[0063] Compared with the prior art, the present invention has at least the following beneficial effects:

[0064] The composite anode material provided in this application includes carbon materials and silicon-based materials. At least a portion of the pores in the carbon material have a gradually decreasing pore size from the surface to the interior, which facilitates gas diffusion into the pores of the carbon material. This allows the silicon-based material to uniformly and effectively fill the pores of the carbon material, ensuring that the open porosity of the pores in the composite anode material is within a suitable range. The silicon-based material filling the pores of the carbon material increases the specific capacity of the composite anode material. Furthermore, the reduced porosity after filling the carbon material with silicon increases the density of the composite anode material and improves the structural stability of the particles. The suitable open porosity also provides expansion space for the silicon-based material, reducing the collapse of the material structure caused by volume expansion during lithium insertion / extraction, effectively reducing side reactions, and thus improving the cycle performance of the material.

[0065] In the above-mentioned method for preparing composite anode materials, a vapor deposition process is used to fully fill the pores of carbon materials with silicon-based materials to prepare the composite anode material. In this method, the pore size of at least a portion of the pores in the carbon material gradually decreases from the surface to the interior. Under negative pressure, when a reaction gas containing silicon source gas is introduced, a certain pressure difference exists between the inner and outer surfaces of the carbon material particles. This facilitates the penetration of the reaction gas containing silicon source gas into the interior of the carbon material particles, thereby deeply guiding the reaction gas into the pores of the carbon material. This allows the silicon-based material to uniformly and effectively fill the pores of the carbon material. Because the pore size gradually decreases from the surface to the interior of the carbon material, the deposition of silicon source gas on the carbon material surface can be effectively reduced, thus reducing the problem of pore closure caused by silicon source gas deposition. Furthermore, the synergistic effect of silicon source gas and hydrogen can better control the gas reaction rate during the deposition process, thereby controlling the deposition rate of the silicon-based material. This ensures that the silicon-based material can uniformly fill the pores of the carbon material, thus guaranteeing that the porosity of the pores in the composite anode material is within a suitable range, thereby improving the specific capacity and structural stability of the composite anode material. Attached Figure Description

[0066] Figure 1 A schematic diagram showing the relationship between the diameter and spacing of three holes that are not on the same straight line in a carbon material provided in this application embodiment;

[0067] Figure 2 A schematic diagram showing the relationship between the pore diameter and pore spacing of three pores that are not on the same straight line in the composite negative electrode material provided in the embodiments of this application;

[0068] Figure 3 A schematic flowchart illustrating the preparation method of the composite negative electrode material provided in the embodiments of this application;

[0069] Figure 4 This is a comparison of the adsorption curves of the composite anode material after carbon material raw material and silicon-based material deposition provided in Example 1 of this application. Detailed Implementation

[0070] To better understand the technical solution of the present invention, the embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0071] It should be understood that the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0072] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0073] It should be understood that the term "and / or" used in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.

[0074] Chemical vapor deposition (CVD) involves placing carbon materials in one or more precursor gases, and under set temperature and pressure conditions, allowing the precursor gases to react and / or decompose on the surface of the carbon materials to produce the desired deposits. Currently, using CVD to deposit Si particles into carbon materials can yield high-performance composite anode materials.

[0075] In CVD processes, mass transfer of gaseous precursors in carbon materials primarily relies on diffusion, resulting in a densification gradient along the gas diffusion direction in the composite anode material. Since the surface of the carbon material comes into contact with the reactant gas first, the deposited products preferentially settle on the surface. Consequently, the reactant gas intended to diffuse deep into the pores of the carbon material is depleted, potentially leading to premature closure of the pores. This weakens the gas's ability to diffuse into the pores and may even cut off the gas supply to the interior, creating a "bottleneck effect" that blocks the mass transfer channels into the internal pores. Consequently, the composite anode material contains residual porosity, affecting deposition quality. Improving the density of the carbon material, the deposition rate of the reactant gas, and reducing the density gradient within the material are among the key issues that urgently need to be addressed in the research and application of composite anode materials.

[0076] This application provides a composite anode material comprising a carbon material and a silicon-based material. The carbon material has pores, at least a portion of which have a gradually decreasing pore size from the surface to the interior of the carbon material. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 2% to 20%.

[0077] In the particle structure of the composite anode material in this embodiment, the pore size of at least some of the pores in the carbon material gradually decreases from the surface to the interior, which is conducive to the diffusion of gas into the interior of the carbon material. This allows the silicon-based material to be uniformly and effectively filled into the pores of the carbon material, thereby ensuring that the open porosity of the pores in the composite anode material is within a suitable range. The filling of the pores of the carbon material with silicon-based material can, on the one hand, increase the specific capacity of the composite anode material, and on the other hand, the reduced porosity of the carbon material after filling with silicon-based material can increase the density of the composite anode material and improve the structural stability of the particles. The open porosity within a suitable range can also provide expansion space for the silicon-based material, reducing the collapse of the material structure caused by volume expansion during lithium insertion and extraction, effectively reducing the occurrence of side reactions, and thus improving the cycle performance of the material.

[0078] In some embodiments, the open porosity of the pores in the composite anode material is 2% to 20%, specifically 2%, 3%, 4%, 5%, 8%, 10%, 12%, 15%, 16%, 17%, 18%, 19%, or 20%, etc., and other values ​​within the above range are also possible, without limitation. It should be noted that the open porosity of the pores in the composite anode material refers to the volume ratio of open pores to the total pore volume in the composite anode material, including both open and closed pores. If the open porosity is too high, it indicates that most of the pores in the carbon material are not effectively filled, resulting in insufficient silicon-based material deposition efficiency. If the open porosity is too low, it indicates that the pore filling rate in the carbon material is high, and there is insufficient pore space in the composite anode material to buffer the volume expansion of the silicon-based material during lithium insertion / extraction. Thus, during lithium insertion / extraction, the volume expansion of the silicon-based material causes excessive expansion pressure within the material structure, leading to structural instability and deterioration of the electrochemical performance of the composite anode material. Therefore, controlling the open porosity of the composite anode material within the aforementioned range is beneficial in two ways: firstly, it improves the specific capacity of the composite anode material; secondly, the reduced porosity after carbon material fills the silicon-based material increases the density of the composite anode material and enhances the structural stability of the particles. A suitable open porosity range also provides expansion space for the silicon-based material, reducing the collapse of the material structure caused by volume expansion during lithium insertion / extraction, effectively reducing side reactions, and thus improving the material's cycle performance. Furthermore, finding a balance between volumetric energy density, rolled particle strength, and particle stability during cycling comprehensively improves the various performance aspects of the anode material.

[0079] In some embodiments, the specific surface area of ​​the carbon material is 300 m². 2 / g~2500m 2 / g. Specifically, the specific surface area of ​​carbon materials can be 300m². 2 / g、500m 2 / g, 1000m 2 / g, 1500m 2 / g、2000m 2 / g、2100m 2 / g、2200m 2 / g、2300m 2 / g、2400m 2 / g or 2500m 2 / g, etc., can also be other values ​​within the above range, and are not limited here.

[0080] In some embodiments, the pore volume of all pores in the carbon material is 0.4 cm³. 3 / g~1.8cm 3 / g. Specifically, the pore volume of all pores in the carbon material can be 0.4 cm³. 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g or 1.8cm 3 / g, etc., and of course, it could also be 0.4cm. 3 / g~1.8cm 3 Other values ​​between / g are not limited here.

[0081] In some embodiments, the density of the carbon material is ≤1.50 g / cm³. 3 Specifically, it could be 0.1 g / cm³. 3 0.2g / cm 3 0.3g / cm 3 0.4g / cm 3 0.5g / cm 3 0.6g / cm 3 0.7g / cm 3 0.8g / cm 3 0.9g / cm 3 1.0g / cm 3 1.10 g / cm 3 1.20g / cm 3 1.30g / cm 31.40g / cm 3 Or 1.50g / cm 3 And so on, without limitation. Understandably, carbon materials have a large number of pores, the presence of which reduces the density of carbon materials, and sufficient porosity is conducive to the deposition of silicon-based materials.

[0082] In some embodiments, the silicon-based material includes at least one of amorphous silicon, crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline and amorphous silicon; specifically, the silicon alloy may be a lithium silicon alloy, a magnesium silicon alloy, etc. It should be noted that in some cases, the silicon alloy includes elemental particles and alloys. Preferably, the silicon-based material includes amorphous silicon.

[0083] In some embodiments, the pore density in the carbon material is 1 pore / μm. 2 ~1000 / μm 2 Specifically, the pore density in carbon materials can be 1 pore / μm. 2 5 per μm 2 10 cells / μm 2 20 cells / μm 2 50 cells / μm 2 100 cells / μm 2 150 cells / μm 2 200 / μm 2 300 / μm 2 500 / μm 2 600 / μm 2 700 / μm 2 800 / μm 2 900 / μm 2 Or 1000 / μm 2 "etc." can also be other values ​​within the above range, and no restrictions are imposed here.

[0084] In some embodiments, the average pore size of the carbon material is 0.1 nm to 50 nm, specifically 0.1 nm, 0.5 nm, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm, etc., without limitation. It is understood that the pore size distribution of the carbon material directly affects the deposition of the silicon-based material. If the pore size of the carbon material is too small, it is difficult to deeply introduce the silicon-containing source gas and hydrogen reaction gas into the pores of the carbon material. The silicon-based material is more likely to be deposited on the surface of the carbon material rather than inside the pores, which can easily lead to the premature closure of the pores on the surface of the composite anode material. This results in insufficient silicon-based material content in the composite anode material, thus deteriorating the electrochemical performance of the material. Conversely, if the pore size of the carbon material is too large, its mechanical strength will deteriorate, and the silicon-based material will agglomerate. Furthermore, when the pore size exceeds a certain value, there will be no real improvement in the entry of the silicon-containing source gas and hydrogen reaction gas, which will also lead to poor electrochemical performance of the material.

[0085] In some embodiments, the porosity of the carbon material is 45% to 75%. Specifically, the porosity of the carbon material can be 45%, 48%, 50%, 55%, 57%, 60%, 65%, 68%, 70%, 71%, 72%, 73%, 74%, or 75%, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0086] In some implementations, in carbon materials, such as Figure 1 As shown, for three holes that are not on the same straight line, the diameters of the three holes are d1, d2, and d3, and the hole spacings are l1, l2, and l3, respectively. Let A1 be l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in the range is given by B1 as d1 + d2 + d3 and C1 as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2)2 or l1 2 -(l3 / 2) 2 The maximum value in the range is B1 / C1 > 1, and B1 / A1 ≤ 4.

[0087] Understandably, when B1 / C1 > 1 and B1 / A1 ≤ 4 in carbon materials, it indicates that the pore distribution in the carbon material is neither too concentrated nor too sparse, which is beneficial for the deposition of silicon-based materials within the pores of the carbon material. Controlling B1 / C1 > 1 and B1 / A1 ≤ 4 in carbon materials ensures, on the one hand, that silicon-based materials are fully deposited within the pores of the carbon material, which is beneficial for improving the specific capacity of the material; on the other hand, it reduces excessive deposition of silicon-based materials within the pores of the carbon material, reserving a certain buffer space for the volume expansion of the silicon-based material, alleviating the stress release of the composite anode material, and thus benefiting the improvement of the material's cycle performance.

[0088] In some embodiments, the pores in the carbon material include micropores, mesopores, and macropores, wherein the micropores account for 5% to 70% of the total volume of all pores, the mesopores account for 30% to 90% of the total volume of all pores, and the macropores account for 0% to 5% of the total volume of all pores.

[0089] Specifically, the volume percentage of the micropores in all pores can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, etc., and of course, it can also be other values ​​between 5% and 70%, which are not limited here.

[0090] The volume percentage of the mesopores in all pores can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%, etc., and is not limited here.

[0091] Specifically, the volume percentage of the macropores in all pores can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc., and is not limited here.

[0092] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 2 nm to 20 nm in all mesopores is >90%, specifically 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or 99%, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0093] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 5 nm to 20 nm in all mesopores is 10% to 50%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 46%, 47%, 48%, 49%, or 50%, etc., and of course, other values ​​between 10% and 50% are also possible, which are not limited here.

[0094] Understandably, a suitable pore size distribution in carbon materials helps to form gas-phase mass transfer channels inside the carbon materials during the deposition process, improves the diffusion environment inside the carbon materials, reduces the density gradient of the carbon materials, and thus improves the compactness of the composite anode materials.

[0095] In some embodiments, the cross-section of the pore is funnel-shaped or inverted conical. It is understood that a funnel-shaped or inverted conical pore has a large inlet, allowing the reactant gas containing silicon source gas and hydrogen to be deeply introduced into the pores of the carbon material. This facilitates the deposition of silicon-based materials within the pores of the carbon material and reduces the risk of reactant gas decomposing too quickly on the carbon material surface and depositing there, which could lead to pore closure and insufficient silicon-based material deposition within the pores, thus affecting the structural stability of the composite anode material. In some embodiments, the pore filling rate is ≥70%. Specifically, the pore filling rate can be 70%, 71%, 72%, 73%, 74%, 75%, 80%, 83%, 85%, 87%, 90%, 91%, 93%, 95%, 96%, 97%, or 99%, etc., and other values ​​within the above ranges are also possible and are not limited here. Preferably, the pore filling rate is 80% to 90%. Understandably, a pore filling rate within the above range is beneficial to improving the specific capacity of the composite anode material on the one hand, and to improving the structural stability of the composite anode material on the other hand, thereby reducing the structural collapse of the composite anode material during cycling.

[0096] In some embodiments, the mass percentage of silicon-based material in the composite anode material is 15% to 60%, specifically 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%, etc. Of course, other values ​​within the above range are also possible, and no limitation is made here.

[0097] In some embodiments, the particle size of the silicon-based material is <50nm. Specifically, the particle size of the silicon-based material can be 1nm, 2nm, 3nm, 4nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 46nm, 47nm, 48nm, 49nm, or 50nm, etc., and is not limited here.

[0098] In some embodiments, the silicon-based material includes amorphous silicon. It is understood that the silicon-based material in the composite anode material includes amorphous silicon, which expands isotropically during lithium intercalation, reducing pore structure collapse, suppressing rapid capacity decay, and improving lithium intercalation cycle performance.

[0099] In some embodiments, the specific surface area of ​​the composite negative electrode material is 2m². 2 / g~500m 2 / g. Specifically, the specific surface area of ​​the composite negative electrode material can be 2m². 2 / g、5m 2 / g, 10m 2 / g, 50m 2 / g, 100m 2 / g, 150m 2 / g、200m 2 / g、250m 2 / g、300m 2 / g, 350m 2 / g、400m 2 / g、450m 2 / g or 500m 2 / g, etc., can also be other values ​​within the above range, and are not limited here.

[0100] In some embodiments, the pore volume of the composite negative electrode material is 0.001 cm³. 3 / g~0.6cm 3 / g, specifically 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g or 0.6cm 3 / g, etc., are not limited here. Compared to the pore volume of carbon materials, the pore volume of the composite anode material after incorporating silicon-based materials is significantly reduced, and the density of the composite anode material is increased. At the same time, the composite anode material also reserves an appropriate amount of porosity to alleviate the volume expansion caused by lithium insertion / extraction in silicon-based materials, which is beneficial to improving the cycle performance of the material. Preferably, the pore volume in the composite anode material is 0.05 cm³. 3 / g~0.5cm 3 / g.

[0101] In some embodiments, the volume percentage of pores in the composite negative electrode material is ≤20%. Specifically, the volume percentage of pores in the composite negative electrode material can be 1%, 3%, 5%, 7%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%, etc., and is not limited thereto. Preferably, the volume percentage of pores in the composite negative electrode material is 5% to 15%.

[0102] In some embodiments, the density of the composite anode material is 1.9 g / cm³. 3 ~2.3g / cm 3 Specifically, it could be 1.9 g / cm³. 3 1.95g / cm 3 2.0g / cm 3 2.1g / cm 3 2.15g / cm 3 2.2g / cm 3 2.25g / cm 3 Or 2.3g / cm 3 Of course, other values ​​within the above range are also possible, and no limitation is made here. It can be seen that because the silicon-based material fills the pores of the carbon material, it increases the density of the carbon material, resulting in an overall density of the composite anode material that is 80% to 120% higher than that of the initial carbon material.

[0103] In some embodiments, the porosity of the composite anode material is 5% to 20%. Specifically, the porosity of the composite anode material can be 5%, 6%, 7%, 10%, 12%, 15%, 16%, 17%, 18%, 19%, or 20%, etc., and of course, other values ​​between 5% and 20% are also possible, without limitation. Understandably, due to diffusion limitations and other factors, it is impossible for silicon-based materials deposited in the pores of carbon materials to achieve 100% pore filling. When the porosity is below 5%, the composite anode material does not have enough pores to withstand the volume expansion during charging and discharging; when the porosity is above 20%, on the one hand, the specific capacity of the composite anode material is low due to insufficient Si filling; on the other hand, the large number of pores in the composite anode material leads to poor overall stability, and during the electrode preparation process, the material structure is prone to collapse due to the extremely high pressure generated during the rolling process.

[0104] In some embodiments, the pore size of the composite anode material is D nm, where D ranges from 0.5 to 100. Specifically, the pore size of the composite anode material can be 0.5 nm, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, or 100 nm, etc., and is not limited here.

[0105] In some embodiments, the pore spacing between any two adjacent pores in the composite anode material is L nm, where L ranges from 1 to 300. Specifically, the pore spacing between any two adjacent pores in the composite anode material can be 1 nm, 5 nm, 10 nm, 50 nm, 70 nm, 100 nm, 110 nm, 150 nm, 180 nm, 200 nm, 230 nm, 250 nm, 280 nm, 290 nm, or 300 nm, etc., and of course, it can also be other values ​​between 1 nm and 300 nm, which are not limited here.

[0106] In some embodiments, the pore diameter of the composite negative electrode material is D nm, and the pore spacing between any two adjacent pores is L nm, where L ≥ 4 × D. Specifically, L can be 4 × D, 5 × D, 6 × D, 7 × D, 8 × D, or 10 × D, etc., and is not limited here.

[0107] In some implementations, in the composite anode material, such as Figure 2 As shown, for three holes that are not on the same straight line, the diameters of the three holes are D1, D2, and D3, and the hole spacings are L1, L2, and L3, respectively. Define A2 as L1. 2 -(L2 / 2) 2 L1 2 -(L3 / 2)2 L2 2 -(L1 / 2) 2 L2 2 -(L3 / 2) 2 L3 2 -(L1 / 2) 2 or L3 2 -(L2 / 2) 2 The minimum value of A2 / B2 is D1+D2+D3, and 3 < A2 / B2 < 50. Preferably, 10 < A2 / B2 < 30. Understandably, when A2 / B2 is within the above range, on the one hand, the silicon-based material can be fully deposited in the pores of the carbon material, which is beneficial to improving the specific capacity of the composite anode material; on the other hand, after the silicon-based material is deposited, the composite anode material will leave an appropriate amount of pores inside the material, which can be used to buffer the volume expansion of silicon, thereby improving the cycle performance of the material.

[0108] In some embodiments, the carbon material is tested using an N2 adsorption-desorption method, and it exhibits a peak value Q1 in the range of 2 nm to 50 nm. The composite anode material is also tested using the same N2 adsorption-desorption method, and it exhibits a peak value Q2 in the range of 2 nm to 50 nm, satisfying the relationship Q2 / Q1 ≤ 0.6. Understandably, Q2 / Q1 can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, or 0.6, etc.

[0109] It should be noted that the N2 adsorption-desorption method tests the amount of silicon-based material filling in the composite anode material before and after deposition; that is, the composite anode material here refers to the carbon material after silicon-based material deposition. When the peak values ​​of the carbon material before and after silicon-based material deposition, as tested by the N2 adsorption-desorption method, meet the above relationship in the range of 2nm to 50nm, the silicon-based material can uniformly fill the pores of the carbon material. At this time, a large number of pores in the composite anode material are filled, which on the one hand ensures the structural stability of the material during charge and discharge, and on the other hand, the pores in the composite anode material that are not completely filled can effectively provide expansion space for the surrounding silicon-based material.

[0110] In some embodiments, the differential specific capacity curve (dQ / dV) of the composite anode material does not represent crystalline Li at approximately ~0.44V. 15 The characteristic peaks of Si4 alloy phase formation indicate that Si in the alloy remains amorphous when lithiated to silicon lithium, and crystalline Li is unlikely to form. 15 Si4.

[0111] In some embodiments, the mass percentage of oxygen in the composite anode material is ≤10 wt%. Specifically, the mass percentage of oxygen in the composite anode material can be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%, and is not limited thereto. It is understood that if the mass percentage of oxygen is too high, the silicon-based material in the composite anode material will be partially oxidized, and the pores will be at least partially destroyed, thus affecting the cycle stability of the material. Controlling the mass percentage of oxygen in the composite anode material within the above range ensures that a large amount of inactive SiO2 is not generated in the material, thereby preventing a decrease in the cycle performance of the composite anode material.

[0112] Secondly, this application also provides a method for preparing a composite anode material, such as... Figure 3 As shown, it includes the following steps:

[0113] A porous carbon material is provided, and a reaction gas containing silicon source gas and hydrogen is introduced under a negative pressure environment. Then, a vapor phase deposition is performed on the carbon material to obtain a composite anode material.

[0114] The composite anode material includes carbon material and silicon-based material. The pore size of at least a portion of the pores in the carbon material gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores. The porosity of the pores in the composite anode material is 2% to 20%.

[0115] In the above-mentioned method for preparing composite anode materials, a vapor deposition process is used to fully fill the pores of carbon materials with silicon-based materials to prepare the composite anode material. In this method, the pore size of at least a portion of the pores in the carbon material gradually decreases from the surface to the interior. Under negative pressure, when a silicon-based reactive gas is introduced, a pressure difference exists between the inner and outer surfaces of the carbon material particles. This facilitates the penetration of the silicon-based reactive gas into the interior of the carbon material particles, allowing it to penetrate deeply into the pores of the carbon material. This results in the silicon-based material uniformly and effectively filling the pores of the carbon material, reducing the decomposition of the reactive gas on the carbon material surface and minimizing the deposition of large amounts of silicon-based material. On the surface of carbon materials, insufficient deposition of silicon-based materials within the pores of the carbon materials can be caused. Since the pore size gradually decreases from the surface to the interior of the carbon materials, the deposition of silicon source gas on the carbon material surface can be effectively reduced, thus preventing the pores from becoming blocked. Furthermore, the synergistic effect of silicon source gas and hydrogen can better control the gas reaction rate during the deposition process, thereby controlling the deposition rate of silicon-based materials. This allows the silicon-based materials to uniformly fill the pore structure of the carbon materials, ensuring that the porosity of the pores in the composite anode material is within a suitable range. This improves the specific capacity, density, and structural stability of the composite anode material, thereby enhancing its electrochemical performance.

[0116] The above technical solution is explained below with reference to specific embodiments:

[0117] S101 provides a porous carbon material.

[0118] In some embodiments, the specific surface area of ​​the carbon material is 300 m². 2 / g~2500m 2 / g. Specifically, the specific surface area of ​​carbon materials can be 300m². 2 / g、500m 2 / g, 1000m 2 / g, 1500m 2 / g、2000m 2 / g、2100m 2 / g、2200m 2 / g、2300m 2 / g、2400m 2 / g or 2500m 2 / g, etc., can also be other values ​​within the above range, and are not limited here.

[0119] In some embodiments, the pore volume of all pores in the carbon material is 0.4 cm³. 3 / g~1.8cm 3 / g. Specifically, the pore volume of all pores in the carbon material can be 0.4 cm³. 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g or 1.8cm 3 / g, etc., and of course, it could also be 0.4cm. 3 / g~1.8cm 3 Other values ​​between / g are not limited here.

[0120] In some embodiments, the density of the carbon material is ≤1.50 g / cm³. 3 Specifically, it could be 0.1 g / cm³. 3 0.2g / cm3 0.3g / cm 3 0.4g / cm 3 0.5g / cm 3 0.6g / cm 3 0.7g / cm 3 0.8g / cm 3 0.9g / cm 3 1.0g / cm 3 1.10 g / cm 3 1.20g / cm 3 1.30g / cm 3 1.40g / cm 3 Or 1.50g / cm 3 The specific details are not limited here. Understandably, carbon materials have a large number of pores, which reduces their density, and sufficient porosity is beneficial for the deposition of silicon-based materials. When the density of carbon materials is too high, the porosity decreases, leading to insufficient Si deposition and hindering the effective improvement of the specific capacity of composite anode materials.

[0121] In some embodiments, the pore density in the carbon material is 1 pore / μm. 2 ~1000 / μm 2 Specifically, the pore density in carbon materials can be 1 pore / μm. 2 5 per μm 2 10 cells / μm 2 20 cells / μm 2 50 cells / μm 2 100 cells / μm 2 150 cells / μm 2 200 / μm 2 300 / μm 2 500 / μm 2 600 / μm 2 700 / μm 2 800 / μm 2 900 / μm 2 Or 1000 / μm 2 "etc." can also be other values ​​within the above range, and no restrictions are imposed here.

[0122] In some embodiments, the average pore size of the carbon material is 0.1 nm to 50 nm, specifically 0.1 nm, 0.5 nm, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc. Of course, other values ​​of 0.1 nm to 50 nm are also possible, and no limitation is made here. Understandably, the pore size distribution of carbon materials directly affects the deposition of silicon-based materials. If the pore size of the carbon material is too small, it is difficult to deeply introduce the reactant gas containing silicon source gas into the pores of the carbon material. The silicon-based material is more likely to be deposited on the surface of the carbon material rather than in the pores, which can lead to the premature closure of the pores on the surface of the composite anode material. This results in insufficient silicon-based material content in the composite anode material, thus deteriorating the electrochemical performance of the material. On the other hand, if the pore size of the carbon material is too large, its mechanical strength will deteriorate, and the silicon-based material will also agglomerate. Furthermore, when the pore size exceeds a certain value, the pressure difference effect decreases, which is not conducive to the entry of the reactant gas containing silicon source gas and hydrogen into the pores of the carbon material, resulting in insignificant improvement in the electrochemical performance of the material.

[0123] In some embodiments, the porosity of the carbon material is 45% to 75%. Specifically, the porosity of the carbon material can be 45%, 48%, 50%, 55%, 57%, 60%, 65%, 68%, 70%, 71%, 72%, 73%, 74%, or 75%, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0124] In some implementations, in carbon materials, such as Figure 1 As shown, for three holes that are not on the same straight line, the diameters of the three holes are d1, d2, and d3, and the hole spacings are l1, l2, and l3, respectively. Let A1 be l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in the range is given by B1 as d1 + d2 + d3 and C1 as l2. 2 -(l1 / 2) 2 l2 2 -(l3 / 2) 2 l3 2 -(l1 / 2) 2 l3 2 -(l2 / 2) 2 l12 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The maximum value in the range, and B1 / C1>1, and B1 / A1≤4.

[0125] Understandably, when B1 / C1 > 1 and B1 / A1 ≤ 4 in carbon materials, it indicates that the pore distribution in carbon materials is uniform, and there is no situation where the pore distribution is too concentrated or too sparse, which is conducive to the deposition of silicon-based materials in the pores of carbon materials.

[0126] In some embodiments, the pores in the carbon material include micropores, mesopores, and macropores, wherein the micropores account for 5% to 70% of the total volume of all pores, the mesopores account for 30% to 90% of the total volume of all pores, and the macropores account for 0% to 5% of the total volume of all pores.

[0127] Specifically, the volume percentage of the micropores in all pores can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, etc., and of course, it can also be other values ​​between 5% and 70%, which are not limited here.

[0128] The volume percentage of the mesopores in all pores can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%, etc., and is not limited here.

[0129] Specifically, the volume percentage of the macropores in all pores can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc., and is not limited here.

[0130] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 2 nm to 20 nm in all mesopores is >90%, specifically 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or 99%, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0131] In some embodiments, the pores in the carbon material include mesopores, wherein the volume percentage of pores with a diameter of 5 nm to 20 nm in all mesopores is 10% to 50%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 46%, 47%, 48%, 49%, or 50%, etc., and of course, other values ​​between 10% and 50% are also possible, which are not limited here.

[0132] Understandably, a suitable pore size distribution in carbon materials helps to form gas-phase mass transfer channels inside the carbon materials during the deposition process, improves the diffusion environment inside the carbon materials, reduces the density gradient of the carbon materials, and thus improves the compactness of the composite anode materials.

[0133] In some embodiments, the cross-section of the hole is funnel-shaped or inverted conical. Understandably, funnel-shaped or inverted conical holes have large inlets, allowing the reactant gas containing silicon source gas to be deeply introduced into the pores of the carbon material. This facilitates the deposition of silicon-based materials within the pores of the carbon material and reduces the risk of reactant gas decomposing too quickly on the carbon material surface and depositing there, which could lead to pore closure and insufficient silicon-based material deposition within the pores, thus affecting the structural stability of the composite anode material.

[0134] In some embodiments, the carbon material includes a catalyst located within pores. It is understood that the catalyst located within the pores provides sites for the deposition and decomposition of the silicon-based material into silicon-carbon composites by the reaction gas containing the silicon source gas. The presence of the catalyst in the carbon material facilitates the deposition of the silicon-based material within the pores, promoting deposition of the silicon-based material within the pores of the carbon material rather than on the surface of the carbon material.

[0135] In some embodiments, the catalyst and carbon material can be doped in a liquid phase or a solid phase. For example, carbon particles can be suspended in a doped solution containing the catalyst, followed by solid-liquid separation and drying to obtain the catalyst-containing carbon material. Alternatively, the catalyst can be reacted with a solution containing polymer monomers, followed by polymerization to obtain a catalyst-containing polymer, which can then be further carbonized to obtain the catalyst-containing carbon material. In actual preparation, carbon materials can also be prepared using other methods, which are not limited here.

[0136] In some embodiments, the carbon material includes a catalyst, which includes at least one of Ni, Cu, Fe, Mn, Au, Al, Sn, Pd, Pt, Ru, and Ir. Understandably, the metal catalyst in the carbon material undergoes a eutectic reaction with the silicon source gas, forming a liquid alloy. At a certain deposition temperature, the liquid alloy crystallizes to precipitate the silicon-based material and the metal catalyst. The presence of the metal catalyst accelerates the hydrosilylation reaction rate, making the reaction of Si-H bonds with unsaturated organic compounds easier. Hydrosilylation refers to the addition of hydrides to unsaturated organic compounds, where the Si-H group forms an addition reaction with the unsaturated carbon-carbon bond. The presence of the metal catalyst significantly lowers the activation energy, making the hydrogenation reaction easier.

[0137] In some embodiments, the catalyst comprises 0.1% to 20% of the carbon material by mass, specifically 0.1%, 0.5%, 1%, 3%, 5%, 7%, 10%, 11%, 15%, 16%, 17%, 18%, 19%, or 20%, etc., and other values ​​between 0.1% and 20% are also possible, without limitation. An appropriate amount of catalyst can serve as an active site for silicon deposition, which is beneficial for the deposition of silicon-based materials within the pores of the carbon material.

[0138] In some embodiments, the carbon material may further include a catalyst precursor comprising a metal salt and / or a metal oxide, wherein the metal comprises at least one selected from Ni, Cu, Fe, Mn, Au, Al, Sn, Pd, Pt, Ru, and Ir.

[0139] In some embodiments, the metal salt includes at least one of halides, nitrates, carbonates, carboxylates, and sulfates.

[0140] In some embodiments, the mass percentage of the catalyst precursor in the carbon material is 0.1% to 10%. Specifically, the mass percentage of the catalyst precursor can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0141] In some embodiments, before introducing the reaction gas containing silicon source gas under negative pressure, the method further includes the following steps: evacuating a vacuum, stopping the evacuation when the deposition pressure of the vapor deposition reaches 0.1 kPa to 50 kPa; and then introducing a protective atmosphere to control the oxygen content in the vapor deposition reaction chamber to be <5%.

[0142] It is understandable that performing a vacuum step before introducing the silicon-containing reaction gas can create a pressure difference between the inner and outer surfaces of the carbon material particles when the silicon-containing reaction gas is introduced, thereby facilitating the penetration of the silicon-containing reaction gas into the interior of the carbon material particles. Introducing a protective atmosphere and controlling the oxygen content in the vapor deposition reaction chamber to be <5%, specifically 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 4.7%, can reduce the oxidation of silicon-based materials in the material to form SiO2. Furthermore, the synergistic effect of the protective atmosphere and hydrogen can better control the gas reaction rate during the deposition process, thereby controlling the deposition rate of silicon-based materials and enabling the silicon-based materials to uniformly fill the pores of the carbon material rather than being deposited on the surface of the carbon material.

[0143] In some embodiments, the steps of evacuation and purging with a protective atmosphere can be repeated multiple times to achieve a pressure of 0.1 kPa to 50 kPa in the reaction chamber, while the oxygen content is <5%.

[0144] S102, under negative pressure, a reaction gas containing silicon source gas is introduced and vapor-phase deposition is performed on carbon material to obtain a composite anode material.

[0145] In some embodiments, the deposition temperature for vapor deposition is 400°C to 650°C. Specifically, the deposition temperature can be 400°C, 420°C, 450°C, 470°C, 490°C, 500°C, 530°C, 550°C, 580°C, 600°C, 610°C, 620°C, 630°C, 640°C, or 640°C, etc., and of course, other values ​​between 400°C and 650°C are also possible, and are not limited here.

[0146] In some embodiments, the heating rate of the vapor deposition is 2℃ / min to 20℃ / min, specifically 2℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 13℃ / min, 15℃ / min, 16℃ / min, 17℃ / min, 18℃ / min, 19℃ / min or 20℃ / min, etc., and is not limited here.

[0147] In some embodiments, the deposition pressure of the vapor deposition is 0.1 kPa to 50 kPa. Specifically, the deposition pressure can be 0.1 kPa, 0.5 kPa, 1 kPa, 5 kPa, 10 kPa, 15 kPa, 20 kPa, 25 kPa, 30 kPa, 35 kPa, 40 kPa, 45 kPa, or 50 kPa, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0148] In some embodiments, the deposition time of the vapor phase deposition is 2h to 1000h. Specifically, the deposition time can be 2h, 5h, 10h, 50h, 100h, 150h, 200h, 250h, 300h, 350h, 400h, 500h, 600h, 650h, 700h, 800h, 900h, or 1000h, etc., and of course, other values ​​between 2h and 1000h are also possible, which are not limited here.

[0149] Understandably, the process conditions of vapor deposition (such as deposition temperature, deposition pressure, and deposition time) will affect the deposition of silicon-based materials in the pores of carbon materials. By controlling the temperature, pressure, and time of vapor deposition within the above range, it can be ensured that the reactive gas containing silicon source gas does not decompose and deposit before entering the pores of carbon materials, but decomposes and deposits rapidly after entering the pores.

[0150] In some implementations, vapor deposition is performed under a protective atmosphere.

[0151] In some embodiments, the protective atmosphere includes at least one of nitrogen, argon, helium, neon, krypton, and xenon.

[0152] In some embodiments, the volume ratio of the protective atmosphere to the reactant gas is 1:10 to 10:1. Specifically, the volume ratio of the protective atmosphere to the reactant gas can be 1:1, 1:2, 1:5, 1:7, 1:8, 1:10, 10:1, 9:1, 6:1, 5:1, 4:1, or 2:1, etc., and is not limited here.

[0153] In some embodiments, the raw materials for the silicon source gas include at least one of silane, disilane, monochlorosilane, dichlorosilane, trichlorosilane, and tetrachlorosilane. It should be noted that when the raw materials for the silicon source gas are silane, disilane, monochlorosilane, or dichlorosilane, it is gaseous at room temperature; when the raw materials for the silicon source gas are trichlorosilane or tetrachlorosilane, it is liquid at room temperature. During the vapor deposition process, the liquid silicon source gasifies into a gaseous silicon source.

[0154] In some embodiments, the volume percentage of hydrogen in the reaction gas containing silicon source gas and hydrogen is 50% to 98%, specifically 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98%, and other values ​​within the above range are also possible and are not limited here. If the mass percentage of hydrogen is too low, the decomposition rate of the gaseous silicon source is too fast, and it is easy to decompose and deposit rapidly on the surface of carbon materials, thus causing pore sealing problems; if the volume percentage of hydrogen is too high, although the reaction process can be well controlled, the decomposition rate of the gaseous silicon source is too slow, thus affecting the deposition efficiency. Therefore, by controlling the volume percentage of hydrogen to 50%–98%, the decomposition rate of the gaseous silicon source can be controlled under the synergistic effect of the protective atmosphere and hydrogen, thereby controlling the deposition rate of silicon-based materials. This allows the silicon-based materials to fill the pores of carbon materials uniformly and effectively, reducing the problem of the gaseous silicon source decomposing too quickly and depositing on the surface of carbon materials, which would lead to the pores in the carbon materials being sealed.

[0155] In some embodiments, the method further includes cooling, washing and drying the reaction products of vapor deposition to obtain a composite anode material.

[0156] In some implementations, the washing method includes ultrasonic cleaning.

[0157] In some embodiments, the washing solvent includes anhydrous ethanol.

[0158] In some implementations, the washing time is 30 min to 60 min, specifically 30 min, 35 min, 40 min, 45 min, 50 min, 51 min, 53 min, 55 min, 56 min, 57 min, 58 min, 59 min or 60 min, and of course other values ​​within the above range are also possible, which are not limited here.

[0159] In some embodiments, the drying time is 20 min to 100 min. Specifically, the drying time can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, or 100 min, etc., and is not limited here.

[0160] In some embodiments, the drying temperature is 70°C to 90°C, specifically 70°C, 75°C, 80°C, 81°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, and of course other values ​​between 70°C and 90°C are also possible, which are not limited here.

[0161] The open porosity of the composite anode material prepared in this embodiment is 2% to 20%, specifically 2%, 3%, 4%, 5%, 8%, 10%, 12%, 15%, 16%, 17%, 18%, 19%, or 20%, etc., and is not limited here. If the open porosity is too large, it indicates that the amount of silicon-based material filling the carbon material is too small, resulting in a low specific capacity of the composite anode material. In addition, too many pores in the composite anode material can easily affect the overall structural stability of the material. If the open porosity is too small, it indicates that the silicon-based material filling the carbon material is too large, resulting in too little pore space for buffering volume expansion. The composite anode material does not have enough pore space to withstand the volume expansion during the charging and discharging process. Moreover, in reality, due to diffusion limitations and other factors, it is impossible for the open pores of the carbon material to be 100% filled with Si. Therefore, controlling the porosity of the pores in the composite anode material between 2% and 20% can, on the one hand, allow the silicon-based material to fully fill the pores of the carbon material, thereby improving the specific capacity of the material; on the other hand, it retains a certain amount of pore space to buffer volume expansion without causing a significant reduction in the structural stability of the material, thus resulting in better overall performance of the material.

[0162] In some embodiments, the method further includes: performing a surface coating treatment on the composite negative electrode material obtained above to form a coating layer on the surface of the composite negative electrode material, thereby obtaining a composite negative electrode material with a coating layer on the surface.

[0163] Understandably, during the aforementioned surface coating process, the coating material covers the surface of the composite anode material, causing some of the open pores on the surface of the composite anode material to be covered by the coating material. The remaining pores can alleviate the volume expansion of silicon. Furthermore, during the vapor deposition process, it is difficult to ensure that all silicon-based materials are deposited inside the composite anode material. Therefore, the coating layer can also cover and protect a small number of exposed Si particles on the surface of the composite anode material. This reduces the direct contact between Si particles and the electrolyte without affecting lithium-ion transport, which is beneficial for the formation of a thinner SEI film when the material comes into contact with the electrolyte. This results in less electrolyte consumption, better cycle retention, and lower volume expansion, and can also improve the specific capacity of the material.

[0164] In some embodiments, the coating material includes at least one of carbon materials, metal oxide materials, polymer materials, and nitride materials.

[0165] In some embodiments, the carbon material includes at least one of soft carbon, hard carbon, crystalline carbon, and amorphous carbon.

[0166] In some embodiments, the metal oxide material includes at least one oxide selected from Sn, Ge, Fe, Si, Cu, Ti, Na, Mg, Al, Ca, and Zn.

[0167] In some embodiments, the nitride material includes at least one of silicon nitride, aluminum nitride, titanium nitride, and tantalum nitride.

[0168] In some embodiments, the polymer material includes at least one of polyaniline, polyacrylic acid, polyurethane, polydopamine, polyacrylamide, sodium carboxymethyl cellulose, polyimide, and polyvinyl alcohol.

[0169] In some embodiments, composite anode materials with a carbon-coated surface are tested using the N2 adsorption-desorption method. These composite anode materials exhibit a peak value Q3 in the range of 2 nm to 50 nm and satisfy the following relationship: Q3 / Q2 ≤ 0.3. Specifically, Q3 / Q2 can be 0.1, 0.15, 0.2, 0.21, 0.22, 0.23, 0.25, 0.26, 0.26, 0.28, 0.29, or 0.3, etc., and is not limited thereto.

[0170] It should be noted that when the peak values ​​of the carbon material after silicon deposition and the anode material after carbon coating, as tested by the N2 adsorption-desorption method, meet the above relationship in the range of 2nm to 50nm, the exposed silicon material on the surface of the carbon material after silicon deposition can be coated by the carbon coating layer. This can reduce the direct contact between the exposed silicon material and the electrolyte, reduce the occurrence of side reactions of the anode material, and improve the structural stability of the anode material after carbon coating during the charging and discharging process.

[0171] This application also provides a battery comprising the aforementioned composite negative electrode material.

[0172] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0173] Example 1

[0174] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the deposition pressure reaches 2 kPa; turn on the CVD furnace and introduce argon gas at a rate of 10 L / min to purify the CVD furnace. At this time, the oxygen content in the furnace is ≤5%.

[0175] (2) The furnace temperature is raised to 400℃ at a heating rate of 10℃ / min, and the vacuum system is restarted to evacuate to 2kPa. At this time, the oxygen content in the furnace is ≤0.5%. Then, the reaction gas is introduced at a rate of 3L / min for chemical vapor deposition for 50h to obtain the reaction product. The reaction gas is a mixture of silane and hydrogen, and the volume ratio of hydrogen in the reaction gas is 55%.

[0176] (3) Introduce argon gas at a rate of 10 L / min, control the partial pressure of argon gas to 0.1 kPa, adjust the pumping speed of the vacuum pump, and control the deposition pressure in the CVD furnace to 2 kPa.

[0177] (4) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the argon supply. Take out the reaction product, ultrasonically clean it with anhydrous ethanol for 20 minutes, and then dry it in an oven at 70°C for 60 minutes to obtain the composite anode material.

[0178] The composite anode material prepared in this embodiment includes carbon material and silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the porosity of the pores in the composite anode material is 10%. The silicon-based material includes amorphous silicon.

[0179] Figure 4 This is a comparison of the adsorption curves of carbon materials before and after the deposition of silicon-based materials, as shown in Example 1 of this application. Figure 4As shown, carbon materials before silicon-based material deposition were tested using the N2 adsorption-desorption method, and the peak value Q1 was found in the range of 2 nm to 50 nm, with Q1 = 0.82. Carbon materials after silicon-based material deposition were tested using the N2 adsorption-desorption method, and the peak value Q2 was found in the range of 2 nm to 50 nm, with Q2 = 0.46 and Q2 / Q1 = 0.56.

[0180] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0181] Example 2:

[0182] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the pressure inside the CVD furnace reaches 6 kPa; turn on the CVD furnace and introduce nitrogen gas at a rate of 2 L / min. At this time, the oxygen content inside the furnace is ≤5%.

[0183] (2) The furnace temperature is raised to 500°C at a heating rate of 5°C / min, and the vacuum system is restarted to evacuate to 6 kPa. At this time, the oxygen content in the furnace is ≤0.5%. Then, the reaction gas is introduced at a rate of 50 L / min for chemical vapor deposition for 20 h to obtain the reaction product. The reaction gas is silane and hydrogen, and the volume ratio of hydrogen in the reaction gas is 75%.

[0184] (3) Introduce nitrogen at a rate of 2L / min, control the nitrogen partial pressure to 0.2kPa, adjust the vacuum pump speed, and control the deposition pressure in the CVD furnace to 8kPa.

[0185] (4) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the nitrogen supply. Take out the reaction product, ultrasonically clean it with anhydrous ethanol for 40 min, and then dry it in an oven at 80°C for 90 min to obtain the composite anode material.

[0186] The composite anode material prepared in this embodiment includes carbon material and silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the porosity of the pores in the composite anode material is 5%. The silicon-based material includes amorphous silicon.

[0187] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0188] Example 3

[0189] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the pressure inside the CVD furnace reaches 10 kPa; turn on the CVD furnace and introduce argon gas at a rate of 16 L / min. At this time, the oxygen content inside the furnace is ≤5%.

[0190] (2) The furnace temperature is raised to 450°C at a heating rate of 15°C / min, and the vacuum system is restarted to evacuate to 10 kPa. At this time, the oxygen content in the furnace is ≤0.5%. Then, the reaction gas is introduced at a rate of 5 L / min for chemical vapor deposition for 6 h to obtain the reaction product. The reaction gas is methane, silicon and hydrogen, and the volume ratio of hydrogen in the reaction gas is 95%.

[0191] (3) Introduce argon gas at a rate of 16 L / min, control the partial pressure of argon gas to 0.15 kPa, adjust the pumping speed of the vacuum pump, and control the deposition pressure in the CVD furnace to 2 kPa.

[0192] (4) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the argon supply. Take out the reaction product, clean it with anhydrous ethanol by ultrasonication for 30 minutes, and then dry it in an oven at 80°C for 30 minutes to obtain the composite anode material.

[0193] The composite anode material prepared in this embodiment includes carbon material and silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the porosity of the pores in the composite anode material is 15%. The silicon-based material includes amorphous silicon.

[0194] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0195] Example 4

[0196] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the pressure inside the CVD furnace reaches 5 kPa; turn on the CVD furnace and introduce nitrogen gas at a rate of 15 L / min to purify the CVD furnace. At this time, the oxygen content inside the furnace is ≤5%.

[0197] (2) The furnace temperature is raised to 650°C at a heating rate of 10°C / min, and the vacuum system is restarted to evacuate to 5 kPa. At this time, the oxygen content in the furnace is ≤0.5%. Then, the reaction gas is introduced at a rate of 20 L / min for chemical vapor deposition for 5 h to obtain the reaction product. The reaction gas is methane, silicon and hydrogen, and the volume ratio of hydrogen in the reaction gas is 60%.

[0198] (3) Introduce nitrogen at a rate of 12 L / min, control the partial pressure of nitrogen to 0.08 kPa, adjust the pumping speed of the vacuum pump, and control the deposition pressure in the CVD furnace to 1 kPa.

[0199] (4) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the nitrogen supply. Take out the reaction product, ultrasonically clean it with anhydrous ethanol for 35 minutes, and then dry it in an oven at 90°C for 80 minutes to obtain the composite anode material.

[0200] The composite anode material prepared in this embodiment includes carbon material and silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the porosity of the pores in the composite anode material is 16%. The silicon-based material includes amorphous silicon.

[0201] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0202] Example 5

[0203] Unlike Example 1, a porous carbon material was selected, and the specific parameters of the pore structure of the carbon material are shown in Table 1.

[0204] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 15%. The silicon-based material includes amorphous silicon.

[0205] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0206] Example 6

[0207] Unlike Example 1, a porous carbon material was selected, and the specific parameters of the pore structure of the carbon material are shown in Table 1.

[0208] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 4%. The silicon-based material includes amorphous silicon.

[0209] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0210] Example 7

[0211] Unlike Example 1, a porous carbon material was selected, and the specific parameters of the pore structure of the carbon material are shown in Table 1.

[0212] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 8%. The silicon-based material includes amorphous silicon.

[0213] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0214] Example 8

[0215] Unlike Example 1, a porous carbon material was selected, and the specific parameters of the pore structure of the carbon material are shown in Table 1.

[0216] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 20%. The silicon-based material includes amorphous silicon.

[0217] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0218] Example 9

[0219] Unlike Example 1, a porous carbon material was selected, and the specific parameters of the pore structure of the carbon material are shown in Table 1.

[0220] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 18%. The silicon-based material includes amorphous silicon.

[0221] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0222] Example 10

[0223] The difference from Example 1 is:

[0224] (3) Introduce argon gas at a rate of 50 L / min, control the partial pressure of argon gas to 10 kPa, adjust the pumping speed of the vacuum pump, and control the deposition pressure in the CVD furnace to 50 kPa.

[0225] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 19%. The silicon-based material includes amorphous silicon.

[0226] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0227] Example 11

[0228] The difference from Example 1 is:

[0229] After step (4), the prepared composite anode material is subjected to surface coating treatment to obtain a composite anode material with a coating layer on the surface.

[0230] The composite anode material prepared in this embodiment includes a carbon material, a silicon-based material, and a carbon coating layer. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 10%. The carbon coating layer is located on the surface of the carbon material and / or the silicon-based material and has a thickness of 50 nm. The silicon-based material includes amorphous silicon.

[0231] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0232] Example 12

[0233] The difference from Example 1 is:

[0234] (2) The furnace temperature is raised to 700℃ at a heating rate of 10℃ / min, and the vacuum system is restarted to evacuate to 2kPa. At this time, the oxygen content in the furnace is ≤0.5%. Then, the reaction gas is introduced at a rate of 3L / min for chemical vapor deposition for 50h to obtain the reaction product. The reaction gas is a mixture of silane and hydrogen, and the volume ratio of hydrogen in the reaction gas is 55%.

[0235] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the porosity of the pores in the composite anode material is 10%. The silicon-based material includes crystalline silicon.

[0236] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0237] Example 13

[0238] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the deposition pressure reaches 2 kPa; turn on the CVD furnace and introduce argon gas at a rate of 10 L / min to purify the CVD furnace. At this time, the oxygen content in the furnace is ≤5%.

[0239] (2) The CVD furnace is connected in series with an evaporation furnace to transfer SiO2. 1.5 The particles were placed in an evaporation furnace, and the furnace temperature was raised to 1400℃ at a heating rate of 10℃ / min, causing the SiO₂ particles to condense. 1.5 The particles evaporate into a gaseous state.

[0240] (3) At the same time, the temperature of the CVD furnace is raised to 650°C at a heating rate of 10°C / min, and the vacuum system is restarted to evacuate to 2 kPa. At this time, the oxygen content in the furnace is ≤0.5%.

[0241] (4) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the argon supply. Take out the reaction product, ultrasonically clean it with anhydrous ethanol for 20 minutes, and then dry it in an oven at 70°C for 60 minutes to obtain the composite anode material.

[0242] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 10%. The silicon-based material includes silicon oxide.

[0243] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0244] Example 14

[0245] (1) Load the porous carbon material into the CVD furnace, evacuate the CVD furnace to remove the air inside the CVD furnace, and stop evacuating when the deposition pressure reaches 2 kPa; turn on the CVD furnace and introduce argon gas at a rate of 10 L / min to purify the CVD furnace. At this time, the oxygen content in the furnace is ≤5%.

[0246] (2) The CVD furnace is connected in series with an evaporation furnace. First, Al particles are placed in the evaporation furnace and the furnace temperature is raised to 1200℃ at a heating rate of 10℃ / min, so that the Al particles evaporate into a gaseous state.

[0247] (3) At the same time, the temperature of the CVD furnace is raised to 500℃ at a heating rate of 10℃ / min, and the vacuum system is restarted to evacuate to 2kPa. At this time, the oxygen content in the furnace is ≤0.5%.

[0248] (4) The CVD furnace is connected in series with an evaporation furnace. The Si particles are then placed in the evaporation furnace, and the furnace temperature is raised to 2700℃ at a heating rate of 10℃ / min, so that the Si particles evaporate into a gaseous state.

[0249] (5) At the same time, the temperature of the CVD furnace is raised to 500℃ at a heating rate of 10℃ / min, and the vacuum system is restarted to evacuate to 2kPa. At this time, the oxygen content in the furnace is ≤0.5%.

[0250] (6) The CVD furnace temperature is further increased to 700℃ at a heating rate of 10℃ / min. The vacuum system is restarted and the vacuum is evacuated to 2kPa. At this time, the oxygen content in the furnace is ≤0.5%, so that Si and Al react to form Al-Si alloy.

[0251] (7) Stop the power supply and close the vacuum system. When the pressure inside the CVD furnace is normal, open the vent valve. After the temperature inside the CVD furnace cools down to room temperature, stop the argon supply. Take out the reaction product, ultrasonically clean it with anhydrous ethanol for 20 minutes, and then dry it in an oven at 70°C for 60 minutes to obtain the composite anode material.

[0252] The composite anode material prepared in this embodiment includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least a portion of the pores gradually decreases from the surface of the carbon material to the interior. At least a portion of the silicon-based material fills the pores, and the open porosity of the pores in the composite anode material is 10%. The silicon-based material includes a silicon alloy.

[0253] The parameters of the composite anode material in this embodiment are detailed in Table 2.

[0254] Comparative Example 1

[0255] The difference from Example 1 is:

[0256] The reaction gas introduced in step (2) contains only silane and no hydrogen.

[0257] The composite anode material obtained in this comparative example includes a carbon material and a silicon-based material, and a carbon coating layer. The carbon material has pores with the pore diameter gradually increasing from the surface to the interior of the carbon material. The porosity of the pores in the composite anode material is 0.5%. The carbon coating layer is located on the surface of the carbon material and / or the silicon-based material and has a thickness of 50 nm.

[0258] Comparative Example 2

[0259] The difference from Example 1 is:

[0260] Step (1) does not involve vacuuming.

[0261] The composite anode material obtained in this comparative example includes a carbon material and a silicon-based material, and a carbon coating layer. The carbon material has pores with the pore diameter gradually increasing from the surface to the interior of the carbon material. The porosity of the pores in the composite anode material is 0.8%. The carbon coating layer is located on the surface of the carbon material and / or the silicon-based material and has a thickness of 50 nm.

[0262] Performance testing

[0263] (1) Test method for specific surface area of ​​composite negative electrode materials or carbon materials:

[0264] The specific surface area was measured using a McTriStar3000 specific surface area and pore size analyzer from the USA.

[0265] (2) Test method for density of composite negative electrode materials or carbon materials:

[0266] The powder is placed in an environment filled with N2, the amount of nitrogen gas replaced is measured, and then the density is calculated.

[0267] (3) Test method for pore volume of composite negative electrode materials or carbon materials:

[0268] The tests were conducted using an ASAP2460 instrument from Microtek (USA). The pore volume V was determined using the BJH Desorption Cumulative Volume of Pores model. Calculated within the aperture range.

[0269] Micropore and mesopore analyses were performed using Micromeretics ASAP 2460. At liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on an object's surface is related to its pore size and other characteristics. By combining the relationship between adsorption amount and relative pressure during the adsorption process, various models can be fitted to calculate the pore size. The software report uses density functional theory (DFT) to calculate the pore size distribution, total pore volume, and pore volume within a certain range.

[0270] The true density P of the negative electrode material is tested, and the porosity of the negative electrode material is calculated as V / (V+1 / P).

[0271] (4) Methods for testing the pore size of composite negative electrode materials or carbon materials:

[0272] Take an appropriate amount of sample particles and measure the pore diameter, pore spacing, and pore diameter variation along the particle surface to the center under a transmission electron microscope (TEM) (SEM can also be used).

[0273] (5) Test method for pore distribution density of carbon materials:

[0274] After processing a suitable amount of sample particles, the pore distribution density in the carbon material is obtained by measuring the number of pores per unit area on the cross-section of the carbon material.

[0275] (6) Test method for the mass content of silicon-based materials in composite anode materials:

[0276] The mass of the composite anode material is M1, and the mass of the material after etching the silicon-based material is M2. (M1-M2) / M1 is the mass content of the silicon-based material in the composite anode material.

[0277] (7) Test method for pore filling rate of carbon materials:

[0278] Before etching the active material in the composite anode material, the volume of the pores in the material is measured as V1. After etching the silicon-based material, the volume of the pores is measured as V2. (V2-V1) / V2 is the filling rate of the silicon-based material in the pores of the carbon material.

[0279] (8) Electrochemical performance testing

[0280] 1) The test method for initial discharge specific capacity and initial coulombic efficiency (ICE) is as follows: A negative electrode slurry is prepared by mixing composite negative electrode material, conductive carbon black, and polyacrylic acid (PPA) in a mass ratio of 75:15:10. This slurry is then coated onto copper foil and dried to form a negative electrode sheet. A lithium metal sheet is used as the counter electrode, and the coin cell is assembled in an argon-filled glove box. The coin cell is then charged and discharged at a current density of 0.1C within a charge-discharge range of 0.01V-5V to obtain the initial discharge specific capacity and initial coulombic efficiency (ICE) of the coin cell.

[0281] 2) The test method for capacity retention and electrode thickness expansion rate after 50 cycles is as follows: A negative electrode slurry is prepared by mixing composite negative electrode material, conductive carbon black (Super-P), conductive graphite (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 92:2:2:2:2. This slurry is then coated onto copper foil and dried to form the negative electrode sheet. The proportions of Si-C and graphite in the composite negative electrode material and graphite mixture with carbon coating are determined by their initial reversible specific capacity and the required combined capacity. A coin cell is assembled using a lithium metal sheet as the counter electrode in an argon-filled glove box. The coin cell is subjected to 50 repeated charge-discharge cycles at a current density of 1C within a charge-discharge range of 0.01V-5V to obtain the capacity retention and electrode thickness expansion rate after 50 cycles.

[0282] (9) Test methods for the porosity of composite negative electrode materials or carbon materials:

[0283] a. First, use an electronic balance to measure the mass M1 (g) of the sample in air;

[0284] b. Place the sample in molten paraffin under vacuum, ensuring the paraffin completely fills the pores of the sample. After soaking for 1 hour until fully saturated, remove the sample and carefully wipe off the paraffin from the surface. Then, use an electronic balance to measure the mass M2 (g) of the sample in air.

[0285] c. Place the paraffin-filled sample on a hanger, immerse it in water, and weigh it. The mass is M3 (g).

[0286] d. Immerse the unsampled hanging device in water and weigh it; the mass is M4 (g).

[0287] The porosity of the sample is calculated using the following formula:

[0288]

[0289] The open porosity of the sample can be calculated using the following formula:

[0290]

[0291] In the formula, ρ S The density (g / cm³) of the corresponding dense solid of carbon materials 3 ), ρ L The density of water (g / cm³) 3 ), ρ ME The density of paraffin (g / cm³) 3 ).

[0292] Table 1 Parameters of carbon materials

[0293]

[0294]

[0295] Table 2 Parameters of Composite Anode Materials

[0296]

[0297] Table 3. Performance test results of the examples and comparative examples.

[0298]

[0299]

[0300] As shown in Tables 1-3, the composite anode material prepared in this embodiment exhibits high initial discharge specific capacity, high initial coulombic efficiency, and high capacity retention after 50 cycles, with low electrode thickness expansion after 50 cycles. This is because in the particle structure of the composite anode material prepared in this embodiment, the pore size of at least some of the pores in the carbon material gradually decreases from the surface to the interior, allowing the silicon-based material to fill the pores of the carbon material uniformly and effectively. This ensures that the porosity of the pores in the composite anode material is within a suitable range. The silicon-based material filling the pores of the carbon material increases the specific capacity of the composite anode material. Furthermore, the reduced porosity after the carbon material fills the silicon-based material increases the density of the composite anode material, improving the structural stability of the particles. The suitable porosity also provides expansion space for the silicon-based material, reducing the collapse of the material structure caused by volume expansion during lithium insertion / extraction, effectively reducing side reactions, and thus improving the cycle performance of the material.

[0301] As can be seen from the table, compared with Example 1, although the composite anode material of Example 10 has a higher capacity retention rate after 50 cycles, its initial discharge specific capacity is lower. This is because the argon gas flow rate during the preparation process is too large, resulting in an excessively high argon partial pressure, which leads to a slow deposition rate of silicon-based material. At the same deposition time, the slow deposition rate of silicon-based material in carbon material results in a low pore filling rate in carbon material and insufficient deposition of silicon-based material in the pores. Consequently, the specific capacity of the composite anode material is difficult to improve, resulting in a low initial discharge specific capacity of the composite anode material.

[0302] Compared to Example 1, the composite anode material in Comparative Example 1 only contained silane in the reaction gas introduced during the preparation process and did not contain hydrogen. Therefore, the silane decomposed too quickly and deposited on the surface of the carbon material, resulting in the pores on the surface of the carbon material being sealed. The open porosity was only 0.5%, making it difficult for silicon-based materials to be deposited and filled in the pores of the carbon material. The pore filling rate in the carbon material was too low, and the amount of silicon-based material deposited in the pores was too small. As a result, the specific capacity of the composite anode material was difficult to improve, leading to a low initial discharge specific capacity of the material.

[0303] Compared with Example 1, the composite anode material of Comparative Example 2 did not undergo a vacuuming step during preparation, which is not conducive to the deposition of silicon-based materials in carbon materials. The open porosity is only 0.8%, and the silicon-based materials are deposited on the surface of carbon materials, causing the pores on the surface of carbon materials to be closed, making it difficult to deposit silicon-based materials into the pores of carbon materials. The pore filling rate in carbon materials is low, and the amount of silicon-based materials deposited in the pores is too small. As a result, the specific capacity of the composite anode material is difficult to improve, resulting in a low initial discharge specific capacity of the material.

Claims

1. A composite negative electrode material, characterized in that The composite negative electrode material includes a carbon material and a silicon-based material. The carbon material has pores, and the pore diameter of at least part of the pores gradually decreases from the surface to the interior of the carbon material. At least part of the silicon-based material is filled in the pores, and the open porosity of the pores in the composite negative electrode material is 2% to 20%.

2. The composite negative electrode material according to claim 1, characterized in that Includes at least one of the following features (1) to (12): (1) The specific surface area of ​​the carbon material is 300 m 2 / g~2500m 2 / g; (2) The pore volume of all pores in the carbon material is 0.4 cm 3 / g~1.8cm 3 / g; (3) The density of the carbon material is ≤1.50 g / cm 3 ; (4) The distribution density of the pores in the carbon material is 1 / μm 2 ~1000 / μm 2 ; (5) The average pore diameter of the carbon material is 0.1 nm to 50 nm; (6) The porosity of the carbon material is 45% to 75%; (7) The filling rate of the hole is ≥70%; (8) In carbon materials, for three holes that are not on the same line, the pore diameters of the three holes are d1, d2, and d3, and the pore distances are l1, l2, and l3, respectively. Define A1 as l2 2 -(l1 / 2) 2 、l2 2 -(l3 / 2) 2 、l3 2 -(l1 / 2) 2 、l3 2 -(l2 / 2) 2 、l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in, B1 is d1+d2+d3, C1 is l2 2 -(l1 / 2) 2 、l2 2 -(l3 / 2) 2 、l3 2 -(l1 / 2) 2 、l3 2 -(l2 / 2) 2 、l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The maximum value among them, B1 / C1>1, and B1 / A1≤4; (9) The pores in the carbon material include micropores, mesopores and macropores, wherein the volume of the micropores accounts for 5% to 70% of all pores, the volume of the mesopores accounts for 30% to 90% of all pores, and the volume of the macropores accounts for 0% to 5% of all pores; (10) The pores in the carbon material include mesopores, wherein the volume of the mesopores with a pore diameter of 2 nm to 20 nm accounts for >90% of all the mesopores; (11) The pores in the carbon material include mesopores, wherein the volume of the mesopores having a pore diameter of 5 nm to 20 nm accounts for 10% to 50% of the total volume of the mesopores; (12) The cross section of the hole is funnel-shaped or inverted cone-shaped.

3. The composite negative electrode material according to claim 1, characterized in that Includes at least one of the following features (1) to (4): (1) The mass proportion of the silicon-based material in the composite negative electrode material is 15%-60%; (2) The particle size of the silicon-based material is less than 50 nm; (3) The silicon-based material includes at least one of amorphous silicon, crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline silicon and amorphous silicon; (4) The silicon-based material includes amorphous silicon.

4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that Includes at least one of the following features (1) to (11): (1) The specific surface area of ​​the composite negative electrode material is 2m 2 / g~500m 2 / g; (2) The pore volume of the pores in the composite negative electrode material is 0.001 cm 3 / g~0.6cm 3 / g; (3) The volume percentage of pores in the composite negative electrode material is ≤20%; (4) The density of the composite negative electrode material is 1.9 g / cm 3 ~2.3g / cm 3 ; (5) The porosity of the composite negative electrode material is 5% to 20%; (6) The pore size of the composite negative electrode material is D nm, and the value of D ranges from 0.5 to 100; (7) In the composite negative electrode material, the distance between any two adjacent pores is L nm, and the value of L ranges from 1 to 300; (8) The pore diameter of the composite negative electrode material is D nm, and the distance between any two adjacent pores is L nm, where L ≥ 4 × D; (9) In the composite negative electrode material, for three holes that are not on the same straight line, the pore diameters of the three holes are D1, D2, and D3, and the pore distances are L1, L2, and L3, respectively. Define A2 as L1 2 -(L2 / 2) 2 、L1 2 -(L3 / 2) 2 、L2 2 -(L1 / 2) 2 、L2 2 -(L3 / 2) 2 、L3 2 -(L1 / 2) 2 or L3 2 -(L2 / 2) 2 The minimum value in , B2 is D1+D2+D3, and 3<A2 / B2<50; (10) The carbon material is tested by the N2 adsorption-desorption method, and has a peak Q1 in the range of 2nm to 50nm; the composite negative electrode material is tested by the N2 adsorption-desorption method, and has a peak Q2 in the range of 2nm to 50nm, and satisfies the following relationship Q2 / Q1≤0.6; (11) The mass proportion of oxygen in the composite negative electrode material is ≤10 wt%.

5. A method for preparing a composite negative electrode material, characterized in that: The following steps are involved: A carbon material with pores is provided, a reaction gas containing a silicon source gas and hydrogen is introduced under a negative pressure environment, and vapor deposition is performed on the carbon material to obtain a composite negative electrode material; wherein the composite negative electrode material includes a carbon material and a silicon-based material, the pore diameter of at least part of the pores in the carbon material gradually decreases from the surface to the interior of the carbon material, at least part of the silicon-based material is filled in the pores, and the opening porosity of the pores in the composite negative electrode material is 2% to 20%.

6. The preparation method according to claim 5, characterized in that Includes at least one of the following features (1) to (12): (1) The specific surface area of ​​the carbon material is 300 m 2 / g~2500m 2 / g; (2) The pore volume of all pores in the carbon material is 0.4 cm 3 / g~1.8cm 3 / g; (3) The density of the carbon material is ≤1.50 g / cm 3 ; (4) The distribution density of the pores in the carbon material is 1 / μm 2 ~1000 / μm 2 ; (5) The average pore size of the carbon material is 0.1 nm to 50 nm; (6) The porosity of the carbon material is 45% to 75%; (7) The filling rate of the hole is ≥70%; (8) In carbon materials, for three holes that are not on the same line, the pore diameters of the three holes are d1, d2, and d3, and the pore distances are l1, l2, and l3, respectively. Define A1 as l2 2 -(l1 / 2) 2 、l2 2 -(l3 / 2) 2 、l3 2 -(l1 / 2) 2 、l3 2 -(l2 / 2) 2 、l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The minimum value in, B1 is d1+d2+d3, C1 is l2 2 -(l1 / 2) 2 、l2 2 -(l3 / 2) 2 、l3 2 -(l1 / 2) 2 、l3 2 -(l2 / 2) 2 、l1 2 -(l2 / 2) 2 or l1 2 -(l3 / 2) 2 The maximum value among them, B1 / C1>1, and B1 / A1≤4; (9) The pores in the carbon material include micropores, mesopores and macropores, wherein the volume of the micropores accounts for 5% to 70% of all pores, the volume of the mesopores accounts for 30% to 90% of all pores, and the volume of the macropores accounts for 0% to 5% of all pores; (10) The pores in the carbon material include mesopores, wherein the volume of the mesopores with a pore diameter of 2 nm to 20 nm accounts for >90% of all the mesopores; (11) The pores in the carbon material include mesopores, wherein the volume of the mesopores having a pore diameter of 5 nm to 20 nm accounts for 10% to 50% of the total volume of the mesopores; (12) The cross section of the hole is funnel-shaped or inverted cone-shaped.

7. The preparation method according to claim 5, characterized in that Includes at least one of the following features (1) to (10): (1) The deposition temperature of the vapor deposition is 400° C. to 650° C.; (2) The heating rate of the vapor deposition is 2°C / min to 20°C / min; (3) The deposition pressure of the vapor deposition is 0.1 kPa to 50 kPa; (4) The vapor deposition time is 2 hours to 1000 hours; (5) The vapor deposition is carried out under a protective atmosphere; (6) The vapor deposition is carried out under a protective atmosphere, wherein the protective atmosphere comprises at least one of nitrogen, argon, helium, neon, krypton and xenon; (7) The raw material of the silicon source gas includes at least one of monosilane, disilane, monochlorosilane, dichlorosilane, trichlorosilane and tetrachlorosilane; (8) The volume proportion of hydrogen in the reaction gas containing silicon source gas and hydrogen is 50% to 98%; (9) The vapor deposition is carried out under a protective atmosphere, and the volume ratio of the protective atmosphere to the reaction gas is 1:10 to 10:1; (10) Before the reaction gas containing silicon source gas is introduced under the negative pressure environment, the method further includes the following steps: vacuuming, and stopping the vacuuming when the deposition pressure of the vapor deposition reaches 0.1kPa to 50kPa; and then introducing a protective atmosphere to control the oxygen content in the vapor deposition reaction chamber to be less than 5%.

8. The preparation method according to any one of claims 5 to 7, characterized in that The method further comprises the following steps: cooling, washing and drying the reaction product of the vapor deposition to obtain a composite negative electrode material.

9. The preparation method according to claim 8, characterized in that Include at least one of the following features (1) to (5): (1) The washing method includes ultrasonic cleaning; (2) the washing solvent includes anhydrous ethanol; (3) The washing time is 30 min to 60 min; (4) The drying time is 20 min to 100 min; (5) The temperature of the drying process is 70°C to 90°C.

10. A battery, characterized in that: The battery comprises the composite negative electrode material according to any one of claims 1 to 4 or the composite negative electrode material prepared by the method for preparing the composite negative electrode material according to any one of claims 5 to 9.

Citation Information

Cited By

  • Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN120149366A